Komunikasi Persuasif Orang Tua dan Anak Dalam Melaksanakan Kegiatan Keagamaan di Dusun III Desa Tarai Bangun Kecamatan Tambang Kabupaten Kampar Provinsi Riau - Syazwan Afandi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the persuasive communication strategies used by parents and children in carrying out religious activities in Dusun III, Tarai Bangun Village, Tambang District, Kampar Regency, Riau Province. The type of research employed is qualitative, with data collection techniques including observation, interviews, and documentation. The findings from field research revealed that parents employed four types of persuasive devices: Acceptance, Rejection, Testimonial, and Bandwagon. First, in the Acceptance device, parents conveyed messages using pleasant words or symbols, associating religious activities with happiness and success. Second, the Rejection device utilized messages that evoke fear or concern, but were delivered gently. Third, the Testimonial device involved citing expert opinions or respected community figures as supporting evidence for the parents' religious encouragement. Fourth, the Bandwagon device relied on social influence, with parents offering incentives to children for participating in religious activities—such as praise, gifts, or social gatherings after attending religious events—to strengthen positive motivation for participation. This study shows that these various persuasive devices effectively influenced children to be more actively involved in religious activities. Parents successfully combined positive approaches with emphasis on spiritual, social, and personal values, thereby encouraging children's active participation in religious practices.